New species of Dibamus (Squamata: Dibamidae) from Pulau Nias, Indonesia - Das, I.; Lim, Kelvin K. P. (The Society for the Study of Amphibians and Reptiles, 2005)
A new species of Dibamus from Pulau Nias, located off the southwest coast of Sumatra, Indonesia, is described based on a single specimen previously referred to as Dibamus novaeguineae and Dibamus alfredi. The new species differs from all congeners in the following combination of characters: snout-vent length (SVL) 123.1 mm; body relatively slender, 3.0% SVL, postoculars two; midbody scale rows 22; ventrals 178; subcaudals 37; frontonasal entire; incomplete rostral suture; labial and nasal sutures complete; preanal pores absent; nuchal collar and body band absent; presacral vertebrae 126; postsacral vertebrae 23; and a relatively short tail (12.75% SVL). The new species from Nias further adds to the endemicity of the vertebrate fauna of these islands and calls for more intensive inventories of the isolated islands to the southwest of Sumatra.